Joint distribution of lightning and wind speed and its impact on the transmission system - Xia, Yunfeng; Li, Bin; Zhou, Xuan; Su, Sheng (Frontiers in Energy Research, 2024)
Distribution of lightning plays a key role in lightning protection of transmission lines. The design of wind deviation under lightning overvoltage of transmission tower is an empirical parameter in transmission line design code. Meteorological data of Hong Kong are investigated to analyze joint distribution of lightning and wind speed. It is uncovered that daily cloud to ground (CG) flashes follows Burr distribution, which is highly skewed toward a few days with notable lightning. The lightning and wind follow a Gumbel-Copula joint distribution. According to empirical and theoretical distribution, there are 239 days with more than 1000 CG lightning per day and about 20% of these days are of maximum wind speed around or over 15 m/s. In 5 days with CG lightning above 30, 000, 3 days are of maximum wind speed over 15m/s and the other 2 days are of maximum wind speed over 10m/s, which suggests that the severe convection with squall line contribute much to the likelihood of the days with high wind and lightning storms.